Impact of Flipped Classroom Implementation on Student Learning Outcomes in Kerala State's Higher Secondary Social Science Curriculum (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study aims to investigate the potential benefits of implementing a Flipped Classroom model into language instruction for high school students in Kerala. Students in a Flipped Classroom may study at their own pace while still taking part in live, in-class lectures; it's a hybrid approach that combines online and in-person activities. This paradigm shifts the transmission of basic material to an external location, freeing up classroom time for students to engage in more in-depth knowledge development. The study's pre- and post-test design was a one-group one. Data was collected via examinations and questionnaires. We discovered that the estimated t-value (5.055) was much greater than the t-table value (1.710) after subjecting the data to a t-test. The purpose of this study was to introduce the flipped classroom approach (FCA) to students so that scholars and practitioners could better understand its potential applications. Using a mixed-case study research technique with triangulation, data was acquired via questionnaires and focus groups. On every measure—engagement, usefulness, efficacy, expectation, and satisfaction—the majority of students gave the flipped classroom a good review, and they were also more inclined to recommend it to their peers. The flipped classroom model has many beneficial effects on student learning, including increased motivation, critical thinking, achievement, and group projects.